Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s00397-015-0863-x
|View full text |Cite
|
Sign up to set email alerts
|

Analytical solutions for the flow of Carreau and Cross fluids in circular pipes and thin slits

Abstract: In this paper, analytical expressions correlating the volumetric flow rate to In all the investigated cases, the three methods agree very well. The agreement with the variational method also lends more support to this method and to the variational principle which the method is based upon.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 32 publications
0
69
0
Order By: Relevance
“…Moukhtari and B. Lecampion 2.5) where the dimensionless apparent width-averaged viscosity for parallel plates flow Γ (τ w , n, µ ∞ /µ o ,γ c ) depends non-linearly on the shear stress at the fracture wall τ w = w 2 ∂p ∂x as well as the rheological parameters of the Carreau model. This dimensionless apparent viscosity requires the solution of the rheological equation at the fracture wall in order to obtain the wall shear rateγ w = τ w /µ(γ w ) for a given value of wall shear stress (Sochi 2014(Sochi , 2015 (see appendix A for details). It is interesting to note that an analytical solution exists for the lubrication of a power-law rheology as well as for the Ellis rheological model (Myers 2005).…”
Section: Problem Formulationmentioning
confidence: 99%
See 3 more Smart Citations
“…Moukhtari and B. Lecampion 2.5) where the dimensionless apparent width-averaged viscosity for parallel plates flow Γ (τ w , n, µ ∞ /µ o ,γ c ) depends non-linearly on the shear stress at the fracture wall τ w = w 2 ∂p ∂x as well as the rheological parameters of the Carreau model. This dimensionless apparent viscosity requires the solution of the rheological equation at the fracture wall in order to obtain the wall shear rateγ w = τ w /µ(γ w ) for a given value of wall shear stress (Sochi 2014(Sochi , 2015 (see appendix A for details). It is interesting to note that an analytical solution exists for the lubrication of a power-law rheology as well as for the Ellis rheological model (Myers 2005).…”
Section: Problem Formulationmentioning
confidence: 99%
“…The solution for the uni-dimensional pressure-driven flow of a Carreau fluid between parallel plate can be solved semi-analytically (Sochi 2015). The dimensionless apparent viscosity Γ Ω 2 ∂Π ∂ξ , α, n, µ ∞ /µ o is obtained from the dimensionless shear stress at the…”
Section: Fe Moukhtari and B Lecampionmentioning
confidence: 99%
See 2 more Smart Citations
“…When including extensional rheology effects, it is expected that regions with large variation in pore diameter such as pore throats would be significantly impacted by higher flow velocities, while the stagnant regions become even more stagnant. It might be useful to consider the case of the capillary tube bundle and sphere packs as reference cases for which exact analytical solutions can be computed for certain rheological models like Carreau fluids using the Weissenberg-Rabinowitsch-Mooney-Schofield integral method (Sochi 2015). But also a 3D porous rock should be considered as this work clearly showed that capillary bundles and sphere packs are only limiting cases for flow fields of sandstone rock.…”
Section: Relationship Between Flow Velocity and Shear Rate In Sandstomentioning
confidence: 95%